Studies of the Effects of Co-substrates on Biodegradation Kinetics of 4-Chlorophenol Using Response Surface Methodology (RSM) - Halim, Nurul Nornazifah Abdul; Sam, Suat Peng; Ng, Si Ling (Penerbit Universiti Sains Malaysia, 2019)
This study aimed to investigate the effect of glucose or sucrose as cosubstrate on the kinetics of 4-chlorophenol (4-CP) biodegradation by 4-CP-acclimated activated sludge. The performance of 4-CP biodegradation was enhanced in the presence of co-substrate with greater values of zero-order rate constant observed for sucrose compared to glucose at higher 4-CP concentration. The interaction effects of two factors, namely initial 4-CP and co-substrate concentrations ranging from 100–500 mg l–1 and 0–1000 mg l–1, respectively, on the biodegradation kinetics were examined by using response surface methodology (RSM). For glucose, the kinetics was found dependent on the 4-CP initial concentration. The optimised condition for 4-CP biodegradation in the presence of glucose was: 200 mg l–1 4-CP and 750 mg l–1 glucose with rate constant of 7.630 mg l–1 h–1